The Effect of Prenatal Yoga on Anxiety and Depression in Kudus, Central Java - Yulianti, Ika; Respati, Supriyadi Hari; Sudiyanto, Aris (Journal of Maternal and Child Health, 2018)
Background: Anxiety and depression in pregnancy can lead to low fetal quality, increased risk of pregnancy complication and developmental disorder of the child. Antidepressant treatment may cause recurrence or addiction rate of up to 50%. In theory, yoga can relieve undesirable psychic symptoms such as anxiety and depression during pregnancy. This study aimed to determine the effect of prenatal yoga on anxiety and depression.Subjects and Method: This study was a randomized controlled trial, conducted at Budi Luhur clinic in Kudus, Central Java, from 27 December 2017 to 7 February 2018. A total of 102 pregnant women was selected for this study by simple random sampling. This sample was allocated at random into the intervention group (n1=51) and control group (n2=51). The independent variable was prenatal yoga as the intervention under study. The dependent variables were anxiety and depression. The data were collected by questionnaire. The difference in the dependent variables between the two groups was tested by Mann-Whitney test and multiple linear regression.Results: The mean level of anxiety was lower in the intervention group than the control group both at two weeks after the intervention (b= -9.25; 95% CI= -10.22 to -8.28; p< 0.001) and four weeks after the intervention (b= -5.79; 95% CI= -7.68 to -3.90; p< 0.001). The mean level of depression was lower in the intervention group than the control group both at two weeks after the intervention (b= -10.82; 95% CI= -12.29 to -9.35; p< 0.001) and four weeks after the intervention (b= -2.58; 95% CI= -3.98 to -1.18; p< 0.001).Conclusion: Prenatal yoga intervention can reduce anxiety and depression during pregnancy.Keywords: prenatal yoga, anxiety, depressionCorrespondence: Ika Yulianti. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: ikatamaevan@gmail.com. Mobile: +628115440036.Journal of Maternal and Child Health (2018), 3(2): 100-104https://doi.org/10.26911/thejmch.2018.03.02.02